Role playing activity for students in non-English study program - Irene Brainnita Oktarin (Concept : Community Concern for English Pedagogy and Teaching, 2018)
The researcher conducted research about role playing activity in English for business at Gentiaras College. English for business is a compulsory subject for non-English study program. The purposes of this research are to identify the students’ attitude toward role palying activity in the class and the implementation of role play in the class. The participants of this research are 25 students from management study program who take English for business. Questionnaire and interview are used for collecting the data. Those data were then analyzed and tabulated. The result of this study is most students have positive attitudes to role playing activity during studying English for business. Given situation based on the topics and playing the role in the class makes the students more motivated to speak English. This activity eases them to improve and practice their English speaking ability. Key words: Role playing; English for business; students’ attitude